(untitled) (GnosisWisdom, 2024)
The objective of this article is to determine the calorific value of the forest species Cedrelinga cateniformis D. (Tornillo). Methodology: The methodological design used in the study was experimental, because variables were manipulated while controlling other variables that could influence the results in the laboratory. Results: The crucible weight was 47.16 gr. and the weight of the sawdust was determined during 7 days, where the constant weight is 8.19gr, this was done to determine the calorific value of this species. The microscopic anatomy of Cedrelinga cateniformis D. wood was observed. Plane (A) transversal (25x), B (100x), (C) tangential (100x), (D) radial (100x), (E) length (25x) and (E) fiber width (400x). Finally, the calorific value obtained from sample 1 was 612.42 (Kcal/100g) and sample 2 was 619.27(Kcal/100g). Conclusion: The species Cedrelinga cateniformis D., known as tornillo, is essential for wood production uses, because its sapwood is pinkish and light reddish heartwood that allows its durability to be significant, where the lower calorific value of the species Cedrelinga cateniformis D. is 612.42 (Kcal/100g). While the upper calorific value is 619.27 (Kcal/100g).